Non-destructive testing of metallic materials using passive and active infrared thermography. (20th June 2014) - Bouteille, P.; Legros, G.; Walaszek, H.; Bodnar, J.L.
<x content-type="archive" xml:space="preserve">Abstract</x> In this work, we approach the possibilities of infrared thermography for non-destructive testing of metallic materials. We show that the passive alternative of the method makes it possible to improve detection of surface defects existing in deep-drawn parts and visible to the naked eye. We then show that active infrared thermography, in particular coupled with induction excitation, can replace in certain cases the magnetic particle inspection, allowing the detection of very fine defects in forged parts. Finally, the study of a stepped block confirms the possibilities of active infrared thermography to detect defects not open to the surface and underlying defects.